Natural and Induced Seismicity in the Lake Erie-Lake Ontario Region: Reactivation of Ancient Faults with Little Neotectonic Displacement - Seeber, Leonardo; Armbruster, John (Géographie physique et Quaternaire, 1993)
ABSTRACTThe two most prominent seismic zones in the Lake Erie-Lake Ontario region are associated with the Akron magnetic lineament and with the Clarendon-Linden fault. Both these features are recognized from geophysical data as regional basement structures related to the Grenville collisional orogen. Neotectonic displacement is not geologically evident, although Paleozoic reactivation is manifested by the Clarendon-Linden fault. We have sharpened the definition of seismic zones in the region by introducing newly discovered events, improving constraints on locations and size for many others, and omitting unreliable ones. This seismicity tends to occur on old faults with minor neotectonic displacements. Related conclusions are: 1) neotectonic surface displacement is not necessary for fault capability, 2) seismogenic faults may have geological and/or geophysical expressions, and 3) a stationary moment release at the historic level requires more capable faults than the ones active during the historic period. Waste fluid injection, oil recovery, and salt-brine recovery have been implicated in cases of induced seismicity in the study area and might have contributed a significant portion of the known earthquakes. Fluid is being injected into the basal platform formation at a depth of 1.8 km near Ashtabula, Ohio. In July 1987, about a year after the onset of injection, a mbLg=3.8 main shock occurred within a 60 km wide area with no known prior seismicity. Aftershocks detected by a short-term local seismic network define a vertical left-lateral fault in the basement just below the platform rocks as close as 700 m from the injection well, probably a reactivated pre-existing fault. Subsequent seismicity suggests a westward migration by 5-10 km, possibly along the same fault.